2021
DOI: 10.1186/s40813-021-00212-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in culled sows from Greek herds: prevalence and associations between findings of histopathology, bacteriology and urinalysis

Abstract: Background Urinary tract infections (UTI) of sows characterized by cystitis, which may progress to ureteritis and pyelonephritis, can affect their productivity, longevity and welfare. In this study, we determined the prevalence of UTI by histopathology and bacteriology. Furthermore, we investigated possible associations between histologically confirmed cystitis and the results of urinalysis and urine cultures in culled sows from three farrow-to-finish herds in Greece. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A meaningful diagnostic workup may include an initial ultrasound examination of the urinary bladder that is followed by collecting a urine sample for urine analysis. In a recent study in Greece (Cernat et al, 2021), histologically defined cystitis was associated with proteinuria and decreased urine pH. Sows with proteinuria were 5.2 times more likely to have histological lesions consistent with cystitis compared with sows without proteinuria.…”
Section: Diagnosing Puerperal Diseases Of the Urogenital Tractmentioning
confidence: 92%
See 2 more Smart Citations
“…A meaningful diagnostic workup may include an initial ultrasound examination of the urinary bladder that is followed by collecting a urine sample for urine analysis. In a recent study in Greece (Cernat et al, 2021), histologically defined cystitis was associated with proteinuria and decreased urine pH. Sows with proteinuria were 5.2 times more likely to have histological lesions consistent with cystitis compared with sows without proteinuria.…”
Section: Diagnosing Puerperal Diseases Of the Urogenital Tractmentioning
confidence: 92%
“…The source of pathological vulvar discharge may be a disease of the reproductive or urinary tract, for example, endometritis or cystitis. Infections of the urogenital tract affect almost one in two culled sows (Bellino et al, 2013;Cernat et al, 2021;Tolstrup, 2017). In sows culled because of reproductive failure, cystitis and endometritis can be found in up to 90% (Sipos et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of cystitis in sows has not been standardized. Various criteria, including bacteriuria [ 13 – 17 ], demonstration of nitrite and/or blood using reagent strip tests [ 18 ], macroscopic pathology [ 13 , 15 , 16 , 19 – 22 ], histopathology [ 13 , 16 , 17 , 20 , 23 ] and ultrasound examination have been used as indicators of cystitis/UTI. A resent review suggested that a diagnostic workup may include an initial ultrasound examination of the urinary bladder that is followed by collecting a urine sample for urine analysis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A resent review suggested that a diagnostic workup may include an initial ultrasound examination of the urinary bladder that is followed by collecting a urine sample for urine analysis [ 24 ]. Earlier studies have reported a variable prevalence of cystitis ranging between 27 and 53% based on histopathology [ 13 , 16 , 20 , 23 ], between of 12.2 and 68% based on macroscopic pathological changes [ 13 , 15 , 21 , 22 ], and between 23 and 38% based on bacteriuria [ 13 , 17 , 20 ]. In the studies conducted during the last 20 years E. coli was the predominant species isolated from sow urine [ 13 , 15 , 17 , 21 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%